Pinoy sa Tate, [Part I] Pinoy sa Nuyok - Aguilar, Mila D. ([Quezon City] The Institute, 1992)
Shows the way of life of Filipinos in New York demonstrating love for their country.
VHS.
Kaakibat sa paglikha at taga-interbyu, Ma. Ernie Selvido.
Keywords: Filipinos -- United States; Sociology